FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN MINUM OBAT PENDERITA KUSTA DI KABUPATEN BREBES - Zakiyyah, Naeli Robikhati; BUDIONO SKM, M.Kes(Epid), IRWAN; Zainafree MH.Kes., dr Intan (Unnes Journal of Public Health, 2015)
In 2013 the amount of new cases of leprosy in Brebes district was counted 301 patients, 48 patients of pausi basiller (PB) and 253 patients of multy basiller (MB). Percentage of Release From Treatment for PB was 64.10 % (< target of 90%), whereas for MB was 72.90 % (< target of 95%). The purpose of this study was to analyze the factors associated with patients pursuance in taking medication at Brebes district.This research belongs to explanatory research using cross-sectional research design. Population in this study were 301 people of which they all were lepers in Brebes District in 2013. The samples were 44 people. The data would be analysed using chi square test with the alternative test using Fisher’s exact test (α=0,05). The results showed significant relationship between knowledge (p value=0.000), attitude (p value=0.000), perception (p value=0.013), family support (p value=0.000), and officers support (p value=0,024) towards adherence of medicine taking of lepers in Brebes Distict. Advice for leprosy officers is to continue giving information to society regarding the jeopardy of leprosy and the bad effects of not taking the leprosy medicine regularly. For patients of leprosy, they should routinely take the medicine given by the doctor or care workers. For people, they should not isolate lepers due to the fear of being infected or other reasons. For researcher, hoped to have, and examine other variable of research using other research designs.